Rainwater Harvesting: A Sustainable Water Management Option for Irrigation of Public Parks - Muhammad Sohail Waqas; Muhammad Jehanzeb Masud Cheema; Saddam Hussain; Muhammad Usman Khalid; Muhammad Saadullah Khan (Environmental Sciences Proceedings, 2022)
Water is imperative for life and plays a vital role in sustaining multiple environmental services. Currently, water resources are under stress, and rainwater harvesting (RWH) is one of the solutions available to address water shortages. In this study, the potential of RWH for irrigation and recreational activities in a public park (i.e., Fatima Jinnah Park-Islamabad) is discussed. The soil conservation service-curve number (SCS-CN) method was used to estimate the runoff. Results revealed that annually 1.80 million cubic meters (MCM) runoff is generated at this park. If this runoff volume is accommodated and managed effectively, it can fulfill the requirements of irrigation and other water-related activities. Hence, the adoption of RWH technology is vital for managing water; therefore, this approach should be used to support any policy changes that lead to widespread use of RWH.